A COMPARISON BETWEEN UNMANNED AERIAL VEHICLE AND AERIAL SURVEY ACQUIRED IN SEPARATE DATES FOR THE PRODUCTION OF ORTHOPHOTOS - ABDULRAHMAN, FARSAT HEETO; KATTAN, RAAD AWAD; GILYANA, SAMI MAMLOOK (Journal of Duhok University, 2020)
The Unmanned aerial vehicles (UAV) have become convenient for many applications such as the production of 3D ground models, orthophotos, road maintenance and dam monitoring, etc. The aim of this paper is to investigate the accuracy of the orthophoto obtained from UAV images compared to the existing orthophoto generated from aerial survey conducted by Vossing German Company in Duhok city, 2011 using GPS ground control point as a reference base. A digital elevation model (DEM) of the university campus was created with the UAV vertical images. Low flight height of 80m was used with the rate of 70% forward overlap and 40% side lap. An orthophoto is produced based on this DEM. To assess the accuracy of UAV orthophotos and the existing orthophotos produced from aerial survey, 7 ground control points (GCPs) were distributed and used for processing the orthophoto mosaic and DEM, 12 GCPs were used as check points. The 19 GCPs were accurately measured using GPS-RTK. Discrepancy in horizontal position of the GCPs measured on both orthophotos was obtained relative to the reference GPS base control points.The UAV data were processed and analyzed using two softwares pix4D and Agisoft Photoscan. The RMS errors obtained from both orthophotos is presented relative to the GPS base. Sub-centimetre accuracy for horizontal position was achieved from the UAV orthophoto at low flight altitude.